FIRST EXPERIENCE OF PROLONGED PERSISTENT ATRIAL FIBRILLATION ELIMINATION WITH THORACOSCOPIC RADIOFREQUENCY ABLATION APPLICATION - E. A. Artukhina; A. S. Revishvili; E. S. Malashenko; C. Muneretto (Инновационная медицина Кубани)
In the present article we describe a clinical case demonstrating our first application of thoracoscopic radiofrequency ablation with vacuum technology Estech Cobra Fusion in a patient, 46, with prolonged persistent atrial fibrillation. We discussed actual questions, performance and showed efficiency of thoracoscopic technologies for atrial fibrillation on a beating heart.